Pengembangan Multilingual Guidance Handbook Based on Edutainment untuk Penguatan Karakter Berbahasa di SD Islam Terpadu - Fitri Aulia; Roni Amrullah (RedwhitePress)
The development of Multilingual Guidance Handbook Based On Edutainment are to conducted to answer the PPK program (Character Building Improvement) launched by the Ministry of Education and Culture in 2017. One of the cocurricular and extracurricular activities applied in the PPK implementation model simulation is language and literature development activities. Character building improvement in this handbook has been developed using the daily activity. Based on the results of the analysis of the needs that have been carried out, this handbook is arranged very in accordance with the conditions of the school. The more basic used by edutainment which is learning to play. This handbook has been developed using the daily activity which is overall summarized in 4 themes namely (1) greeting sentence, (2) my family, (3) body member, (4) school equipment. After testing experts, both material experts and display experts concluded that Multilingual Guidance Handbook Based On Edutainment was a good media category. Furthermore, the test in the field obtained results that Multilingual Guidance Handbook Based On Edutainment received an effective response from students.